2019
DOI: 10.12998/wjcc.v7.i21.3524
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal perivascular epithelioid cell tumours: A case report and review of literature

Abstract: BACKGROUNDThe perivascular epithelioid cell tumour (PEComa) family of tumours mainly includes renal and hepatic angiomyolipomas, pulmonary lymphangioleiomyomatosis and clear cell “sugar” tumour of the lung. Several uncommon tumours with similar morphological and immunophenotypical characteristics arising at a variety of sites (abdominal cavity, digestive tract, retroperitoneum, skin, soft tissue and bones) are also included in the PEComa family and are referred to as PEComas not otherwise specified.CASE SUMMAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 61 publications
(74 reference statements)
1
15
1
Order By: Relevance
“…[ 21 ] In addition, PEComa may stem from myoblasts or smooth muscle cells that have mutated at the molecular level, and the pericytes are likely to be the ancestors of PEComa. [ 27 ] The volume of a hepatic PEComa can change over a wide range. Maebayashi et al [ 3 ] examined 74 cases and reported a maximum size of these tumours of 25 cm, and the minimum size was 1.2 cm in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] In addition, PEComa may stem from myoblasts or smooth muscle cells that have mutated at the molecular level, and the pericytes are likely to be the ancestors of PEComa. [ 27 ] The volume of a hepatic PEComa can change over a wide range. Maebayashi et al [ 3 ] examined 74 cases and reported a maximum size of these tumours of 25 cm, and the minimum size was 1.2 cm in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Angiomyolipomas are among the most common form of PEComas, but there are several uncommon forms. Retroperitoneal localisation has recently been established as the third most frequent, but altogether rare PEComa localisation 9…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal dominant mutations of the TSC1 or TSC2 tumor suppressor genes lead to tuberous sclerosis, characterized by a multi-system development of benign tumors (such as subependymal giant cell tumors and cardiac rhabdomyomas), as well as seizures, cognitive delays, and cutaneous findings [9] , [10] , [11] . Some of these were observed in our patient, compatible with a presumptive clinical diagnosis of TSC.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, the main differential is AML, with varying amounts of angiogenic, myogenic, and fatty elements. A fat-rich appearance is most common, though the lesion may often appear with a hyperdense collection obscuring the fatty component due to presence of perirenal or intratumoral hemorrhage [9] . Calcification and necrosis have also been observed, raising the possibility of fat-containing renal cell carcinoma [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation